Emerging biomaterial-based strategies for personalized therapeutic in situ cancer vaccines. (January 2022) - Viswanath, Dixita Ishani; Liu, Hsuan-Chen; Huston, David P.; Chua, Corrine Ying Xuan; Grattoni, Alessandro
Abstract: Landmark successes in oncoimmunology have led to development of therapeutics boosting the host immune system to eradicate local and distant tumors with impactful tumor reduction in a subset of patients. However, current immunotherapy modalities often demonstrate limited success when involving immunologically cold tumors and solid tumors. Here, we describe the role of various biomaterials to formulate cancer vaccines as a form of cancer immunotherapy, seeking to utilize the host immune system to activate and expand tumor-specific T cells. Biomaterial-based cancer vaccines enhance the cancer-immunity cycle by harnessing cellular recruitment and activation against tumor-specific antigens. In this review, we discuss biomaterial-based vaccine strategies to induce lymphocytic responses necessary to mediate anti-tumor immunity. We focus on strategies that selectively attract dendritic cells via immunostimulatory gradients, activate them against presented tumor-specific antigens, and induce effective cross-presentation to T cells in secondary lymphoid organs, thereby generating immunity. We posit that personalized cancer vaccines are promising targets to generate long-term systemic immunity against patient- and tumor-specific antigens to ensure long-term cancer remission.